Engineering a microbiosphere to clean up the ocean – inspiration from the plastisphere - Alnahdi, Khulood A.; Alali, Laila W.; Suwaidan, Mezna K.; Akhtar, M. Kalim (Frontiers in Marine Science, 2023)
Plastic is a ubiquitous material that has become an essential part of our lives. More than one hundred million tons of plastic has accumulated in the world’s oceans as a result of poor waste management. This plastic waste gradually fragments into smaller pieces known as microplastics and nanoplastics. These small plastic particles can cause significant damage to marine ecosystems, and negatively impact human health. According to a recent review of international patents, the majority of ocean-cleaning inventions are limited to microplastics larger than 20 μm. Furthermore, such technologies are ineffective for nanoplastics, which measure less than 1000 nm, or even fibrous plastics. Alternative solutions need to be considered for the large-scale in situ removal of microplastics and nanoplastics from the ocean. In this perspective, we present the concept of engineering a microbial ecosystem, which we term the microbiosphere. The concept is based on key observations that have been made for natural plastic-based ecosystems known as plastispheres. These observations relate to the solid support material, self-sustainability, attachment to plastic, degradation of plastic, and risk of pathogenicity. Inspiration can be taken from the plastisphere whereby a novel microbial ecosystem could be designed and engineered as a bioremediation tool to rid the ocean of micro- and nanoplastics. Such an engineered system could outcompete pathogens for marine plastic waste and potentially reduce the risk of infectious diseases.